Extramedullary plasmacytoma – case report - Díez, L. (2010)
Extramedullary plasmacytoma of the larynx and localized laryngeal amyloidosis are two entities extremely rare in children. We report the case of a child of 11 years with a two months dysphonia and a diagnosis of extramedullary plasmacytoma with localized laryngeal amyloidosis. The treatment and outcome are compared with the few cases found in the literature.